THE RELATIONSHIP BETWEEN PAY SATISFACTION AND QUIET QUITTING-USING ORGANIZATIONAL IDENTIFICATION AS A MODERATOR - Lin, Wen-Hsia; Lin, Chin-Chiuan (International Journal of Application on Economics and Business, 2025)
In an economic downturn, employees may choose to quiet quitting because they cannot easily find new jobs, which may reflect their dissatisfaction with the company culture and pay. Companies and employees have different views on the reasons and solutions for quiet quitting. The reasons leading to quiet quitting might include: dissatisfaction with pay, incompatibility of values, pursuit of work-life balance, etc. The present study aims to investigate the relationship among organizational identification, pay satisfaction, and quiet quitting, taking a traditional food manufacturing company as the case study object. The results of the study found that pay satisfaction has a significant effect on quiet quitting. When employees are more satisfied with their pay levels, they are less likely to quiet quitting. The interaction between pay satisfaction and organizational identification with membership has a significant effect on quiet quitting. When employees are satisfied with their pay and have good relationships with members of the organization, they are less likely to engage in quiet quitting. Therefore, it is recommended that corporate organizations should focus on improving employee pay satisfaction and improving interpersonal relationships within the organization to reduce the risk of quiet quitting.